Effects of gender equality and social costs of failure on early-stage entrepreneurship activity - Sharon Alicia Simmons; Chong Kyoon Lee; Susan Young; Lois Shelton; MaQueba Massey (New England Journal of Entrepreneurship)
Purpose – In this study, we question: how do the social costs of failure interact with gendered institutions to affect the early stage entrepreneurship activity? We address this question by employing the institutional theory and a unique dataset of 286,989 entrepreneurs across 35 countries. Design/methodology/approach – To test our hypotheses, we use a multilevel modeling analysis that nests individual entrepreneurs within the countries. To capture individual and country-level variables, we constructed a unique dataset that combines data from the Global Entrepreneurship Monitor (GEM), European Flash Barometer (EUFB), World Bank Development Indicator (WDI), World Bank Doing Business Report (WBDB) and World Economic Forum (WEF). Findings – Our analysis confirms that higher levels of the country-level gender equality positively correlate with the early-stage entrepreneurship activity of women. Moreover, we find that this positive relationship is amplified in institutional environments with high social costs of failure, suggesting that societal intolerance for failure can exacerbate the negative effect of gender inequality on the participation of women in entrepreneurship. Research limitations/implications – Our research contributes to academic interest on the role of legitimacy in women entrepreneurship and is of particular interest to international business scholars, seeking a better understanding of multidimensional construction of institutional frameworks across countries. In this study, we set out to address an important research question: how do the social costs of failure interact with gendered institutions to affect entrepreneurship activity? Our study provides a comprehensive portrait of gendered institutions by including the framework conditions of education, healthcare and political power. We found that in societies with gender equality, the likelihood of individuals engaging in the early-stage entrepreneurship activity is higher and that the positive relationship is strengthened in national environments with high social costs of failure. Practical implications – Our study findings underscore the need for government policies addressing global gender gaps in economic empowerment. In particular, policies assisting women in obtaining education in high-growth industries like information technology or providing funding to women-dominated industries may foster activity for women seeking to do business in such industries. Such policies connect the early-stage entrepreneurship activities with gender equality concerns and initiatives. Social implications – Regarding the social costs of failure construct, specifically, prior studies generally focus narrowly on the context of failed entrepreneurs. We cast a wider net on men and women entrepreneurs’ entry decisions (irrespective of prior experience with business failure) and provide new views on the effects of social costs of failure on entrepreneurial ecosystems. We also extend the research on the legitimacy of women as entrepreneurs with the gender equality construct. Originality/value – Unlike previous studies, which often focus on the “3Ms” of market, money and management, our research adopts a more holistic perspective. We recognize that the opportunities and challenges faced by entrepreneurs are shaped not only by individual skills and resources but also by the broader macroenvironment. By incorporating the framework conditions of education, healthcare and political power, alongside the intricate interplay of social costs and norms, our study paints a comprehensive picture of the landscape of female entrepreneurship.